Are they being authentic? The effects of self-disclosure and message sidedness on sponsored post effectiveness. Issue 1 (2nd January 2022) - Lee, Susanna S.; Johnson, Benjamin K.
Abstract: The importance of social media for advertising and marketing has brought growing interest and investment into sponsored influencers. However, much is unknown about the effectiveness of influencers, including the mechanisms by which these online personalities build and maintain authentic image. This study examines two important elements, influencers' self-disclosures (present vs. not present) and message sidedness (one-sided vs. two-sided), to explain the effectiveness of influencer marketing. Findings revealed that Instagram product reviews with two-sided messages yielded higher influencer authenticity, influencer credibility, ad attitudes, and eWOM intentions than Instagram product reviews with one-sided messages. Results also revealed that the perceived authenticity and credibility of influencers with two-sided messages mediated effects on ad attitude, brand attitudes, purchase intention, and eWOM intention. Self-disclosure was not impactful, nor did product involvement moderate effects of influencer posts. Theoretical, practical, and managerial implications are considered, indicating that two-sided messages are advantageous for influencers and the brands who sponsor them, while self-disclosure is less consequential.